RUSSIAN ERUPTION WARNING SYSTEMS FOR AVIATION - Neal C.A.; Girina O.A.; Senyukov S.L.; Rybin A.V.; Osiensky J.; Izbekov P.; Ferguson G. (My University, 2009)
More than 65 potentially active volcanoes on the Kamchatka Peninsula and the Kurile Islands pose a substantial threat to aircraft on the Northern Pacific (NOPAC), Russian Trans-East (RTE), and Pacific Organized Track System (PACOTS) air routes. The Kamchatka Volcanic Eruption Response Team (KVERT) monitors and reports on volcanic hazards to aviation for Kamchatka and the north Kuriles. KVERT scientists utilize real-time seismic data, daily satellite views of the region, real-time video, and pilot and field reports of activity to track and alert the aviation industry of hazardous activity. Most Kurile Island volcanoes are monitored by the Sakhalin Volcanic Eruption Response Team (SVERT) based in Yuzhno-Sakhalinsk. SVERT uses daily moderate resolution imaging spectroradiometer (MODIS) satellite images to look for volcanic activity along this 1,250-km chain of islands. Neither operation is staffed 24 h per day. In addition, the vast majority of Russian volcanoes are not monitored seismically in real-time. Other challenges include multiple time-zones and language differences that hamper communication among volcanologists and meteorologists in the US, Japan, and Russia who share the responsibility to issue official warnings. Rapid, consistent verification of explosive eruptions and determination of cloud heights remain significant technical challenges. Despite these difficulties, in more than a decade of frequent eruptive activity in Kamchatka and the northern Kuriles, no damaging encounters with volcanic ash from Russian eruptions have been recorded.
Keywords: 38.37.25 Вулканология; Вулканы Курило-Камчатского региона; Volcanic ash and aircraft safety; Kamchatka volcanoes; Kurile volcanoes; Ash clouds; Volcano hazard warnings; Volcano hazards; Aviation safety